Типові помилки розробників законопроектів - Снігур, І.Й. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
На примерах положений отдельных законопроектов, зарегистрированных в Верховной Раде Украины, автор статьи анализирует типичные ошибки, которые допускают разработчики законопроектов. Акцентируется внимание на необходимости соблюдения правил законодательной техники, а также проверки законопроекта на соответствие действующему законодательству Украины. Оn examples of provisions of separate draft laws registered in Supreme Rada of Ukraine, the author of the article analyzes typical mistakes made by draft laws developers. Need to meet legislative technique rules and to inspect draft law with respect to its correspondence with acting legislation of Ukraine is emphasized.